The Trend of the Hospitality Industry and the Advantages Versus the Disadvantages of Investing in the Workforce - Steluta Radu; Mihaela Constandache; Anca - Cristina Stanciu (Ovidius University Annals: Economic Sciences Series, 2020)
The hospitality industry, although attractive to many entrepreneurs, is among the riskiest areas of activity in Romania. Challenges and risks can occur at any step. The human resource working in the hospitality industry is inadequately prepared, this leads to the failure of hospitality business. That's why the right people, in the right places, responsible people who value work, especially in a field with as many challenges as the hospitality industry, will always remain an essential factor of success. In this research we proposed new measures for the training of the workforce in a system of continuous training carried out by Ministry of Labour and social Protection for vulnerable target groups made up of unemployed and students. The study was carried out by static analysis of the demographic evolution of Romania, the trend of the labour market.